Simulation of Updraft and Downdraft Gasification Using Computational Fluid Dynamics (CFD) for Production of Hydrogen-Rich Syngas from Cow Manure Waste - Amaliyah Rohsari Indah Utami; Anindya Nabila Salma; Daffa Rayhan Betha Muchtar; Neni Sintawardani; Suwandi (Engineering Science Letter, 2025)
Biomass gasification offers a promising route to low‑carbon hydrogen, yet the operating conditions and reactor configuration governing hydrogen-rich syngas remain insufficiently compared across practical regimes. This study aims to quantify the effects of gasifier type (updraft vs. downdraft), operating temperature, and superficial velocity on hydrogen production performance, with emphasis on the syngas H2/CO ratio. Computational fluid dynamics simulations were implemented to model devolatilization, oxidation, and reduction pathways under steady-state assumptions, while systematically varying temperature (680-800°C) and air superficial velocity (0.0025-4 m/s). Model validation against experimental reference data demonstrated good agreement, with relative errors ranging from 5.95% to 6.93%. The results indicate that a downdraft configuration operated at 680°C and 2 m/s maximizes the H2/CO ratio, achieving a value of 2.091, outperforming alternative settings in terms of hydrogen yield and energy efficiency, albeit with higher variability than the updraft configuration. Increasing air flow beyond this optimum diminishes the H2/CO ratio due to enhanced oxidation, whereas raising the temperature to 800°C generally reduces the average H2/CO across both configurations. These findings establish a practical operating window for hydrogen‑rich syngas from livestock waste and highlight the need for rigorous process control to manage variability in downdraft operation. The study provides evidence-based guidance for gasifier design and operation, aiming to achieve efficient and renewable hydrogen production.